2020
DOI: 10.3390/agriculture10070258
|View full text |Cite
|
Sign up to set email alerts
|

Light Quality Affects Growth and Physiology of Carpesium triste Maxim. Cultured In Vitro

Abstract: The objective of this study was to investigate the effect of light quality on the growth and contents of photosynthetic pigments and total flavonoids, the parameters of chlorophyll a fluorescence, antioxidant capacities, and enzyme activities. It was intended to preliminarily explore the internal mechanisms involved for the effect of light quality on the growth and physiology of Carpesium triste Maxim. Stem apex explants were cultured on the Murashige and Skoog (MS) medium under white (W), red (R), blu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 106 publications
2
12
0
Order By: Relevance
“…Earlier reports suggested that the elevated transcriptional regulation of the PAL upon oxidative stress augments the synthesis of secondary metabolites ( Zhan et al, 2012 ). Similarly, the supplementation of combinations of red and blue lights increased the activities of antioxidant enzymes in the in vitro plants of Carpesium triste ( Zhao et al, 2020 ) and in the callus cultures of Cinidium officinale ( Adil et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier reports suggested that the elevated transcriptional regulation of the PAL upon oxidative stress augments the synthesis of secondary metabolites ( Zhan et al, 2012 ). Similarly, the supplementation of combinations of red and blue lights increased the activities of antioxidant enzymes in the in vitro plants of Carpesium triste ( Zhao et al, 2020 ) and in the callus cultures of Cinidium officinale ( Adil et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study also reported that red-light spectrum needed salicylic acid to induce flavonoid synthesis (Ni et al, 2018). However, most former studies on the effects of lighting spectra on flavonoids accumulation were conducted on narrow bandwidth lights, which had only a partial effect on flavonoids synthesis (Zhao et al, 2020). Instead, the wide bandwidth spectrum comprising both red-and blue-light wavelengths had greater impact (Zhao et al, 2020).…”
Section: Secondary Metabolismsmentioning
confidence: 99%
“…A previous study reported the importance of light in antioxidant enzyme metabolism [ 41 ]. For instance, the combination of red and blue light at a ratio of 1:1 enhanced the activity of antioxidant enzymes, including catalase (CAT), peroxidase (POD), superoxide dismutase (SOD), and ascorbate peroxidase (APX), in Carpesium triste Maxim [ 42 ]. Increase in the activity of antioxidant enzymes, such as CAT, was found to be related to the delay in the onset of leaf senescence in C. triste [ 42 ], wheat [ 43 ], pea [ 44 ], and banana [ 45 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, irradiation with blue and red LED combinations resulted in enhanced biomass during the in vitro culture of Achillea millefolium [ 115 ], Densribium [ 1 ], blueberries [ 114 ], sugarcane [ 110 , 116 ], and chrysanthemum [ 26 ]. In addition to biomass, chlorophyll content was increased in different plant species cultured under LED irradiation [ 24 , 42 , 117 , 118 , 119 ]. In similar studies, increased total carotenoid level was reported in shoot cultures irradiated with different LEDs [ 119 , 120 , 121 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation